On Tall Pine Lake - Garlock, Dorothy (New York : Warner Books, 2007)
"A young woman in 1970s Arkansas is charmed by the owner of a fishing camp, but is wary of his potential connections to several local crimes."--Provided by the publisher.
Keywords: Fishing lodges -- Fiction; Arkansas -- Fiction; Fiction